2014
DOI: 10.1659/mrd-journal-d-13-00089.1
|View full text |Cite
|
Sign up to set email alerts
|

Migration as an Adaptation Strategy and its Gendered Implications: A Case Study From the Upper Indus Basin

Abstract: We are grateful to all the respondents and interviewees who provided us with their valuable input on the issue of women's land rights.We are also grateful to Action Aid, IFAD and IDRC for financing this project and extending their support at various stages of the project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 21 publications
4
48
1
Order By: Relevance
“…Systems knowledge et al 2014), and even when migration is directly driven by environmental change, it can still enhance migrant households' adaptive capacities and livelihood resilience through monetary and social remittances (Adger et al 2002;McLeman and Smit 2006;Gioli et al 2014;Gemenne and Blocher 2017).…”
Section: Mountainresearchmentioning
confidence: 99%
“…Systems knowledge et al 2014), and even when migration is directly driven by environmental change, it can still enhance migrant households' adaptive capacities and livelihood resilience through monetary and social remittances (Adger et al 2002;McLeman and Smit 2006;Gioli et al 2014;Gemenne and Blocher 2017).…”
Section: Mountainresearchmentioning
confidence: 99%
“…Studies from Nepal and India have reported local cultural and institutional factors that act as barriers to adaptation, particularly for women (Ahmed and Fajber 2009;Jones and Boyd 2011). Because of women's limited ownership of land, they are still largely excluded from training, extension services, irrigation management, and development schemes intended for farmers (Gioli et al 2014). Despite the policy provisions, realizing adaptation goals for women and socially marginalized groups in the HKH is likely to be very challenging unless there is urgent and more targeted action on the ground to strengthen and improve their access to and control over productive assets, access to formal and non-formal education, mobility, and opportunities to generate income.…”
Section: Public Consultation and Stakeholder Engagement In Adaptationmentioning
confidence: 99%
“…Existing social networks and support systems as well as emergency preparedness and early warning systems influence this spatial distribution (Lu et al 2016b, Mallick 2014. In South Asia, in particular, rural-urban movement in the face of slow or sudden-onset disaster is commonplace (Bryan, Chowdhury, and Mobarak 2014;Deshingkar 2012;Gioli et al 2014). For example, Mallick (2014) finds that almost 25% of households affected by Cyclone Aila moved toward neighboring cities immediately after emergency relief works were phased out.…”
Section: B Disasters In Asiamentioning
confidence: 99%